2015
DOI: 10.1039/c5cc02374b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant controlled regio- and stereodivergent azidohydroxylation of alkenes via I2 catalysis

Abstract: A novel, I2 catalyzed regio- and stereodivergent vicinal azidohydroxylation of alkenes leading to 1,2-azidoalcohols in high yields (up to 92%) and excellent dr (up to 98%) has been developed. This unprecedented transformation employs NaN3 and DMF as N- and O-nucleophiles respectively. The role of DMF as the O-source in the reaction has been unequivocally proven by (18)O labelling studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 40 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Notably, in the latter approach, copper‐based catalysts proved to be unsuccessful. Alternatively, iodine or Sn IV[17a] catalysis using organic peroxides have been employed towards azido alcohols, which, in turn, can then be oxidized to azidoketones with pyridiniumchlorochromate (PCC) …”
Section: Methodsmentioning
confidence: 99%
“…Notably, in the latter approach, copper‐based catalysts proved to be unsuccessful. Alternatively, iodine or Sn IV[17a] catalysis using organic peroxides have been employed towards azido alcohols, which, in turn, can then be oxidized to azidoketones with pyridiniumchlorochromate (PCC) …”
Section: Methodsmentioning
confidence: 99%
“…Vicinal hydroxyazidation of alkenes offers a simpler and more convenient approach for preparing 1,2-azidoalcohols. So far, several effective approaches have been developed for the synthesis of 1,2-azidoalcohols through direct hydroxyazidation of alkenes ( Prasad et al., 2015 ; Sakurada et al., 2000 ). However, stoichiometric or excess oxidants must be used, and these methods are restricted by the specified O-sources.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of IR (band at 2,100 cm −1 ) (Hesse et al, 1997 ) as well as the 13 C NMR spectra of 36–39 confirmed the formation of tertiary azides. Thus, the signals of ( C- OH) carbon atoms were located around δ: 73–79 ( 3 J C−P 19–21 Hz) while signals of C N 3 appeared at δ: 57, similarly to 2-azido-2-phenylpropan-1-ol (Prasad et al, 2015 ). Although 3-hydroxyphosphonates 36–39 can rotate freely around the P-C1 and C1-C2 bonds, we would like to emphasize that in [D] chloroform they exist predominantly as their anti -conformers (arrangement of phosphonate and CH 2 OH moieties regarding C1-C2 bonds) as can be judged from the large (18–21 Hz) values of their 3 J C−P couplings together with the analysis of the NOESY and H-F HOESY spectra.…”
Section: Resultsmentioning
confidence: 97%